2017
DOI: 10.1111/ijlh.12664
|View full text |Cite
|
Sign up to set email alerts
|

Is it acceptable to use coagulation plasma samples stored at room temperature and 4°C for 24 hours for additional prothrombin time, activated partial thromboplastin time, fibrinogen, antithrombin, and D‐dimer testing?

Abstract: Plasma samples stored both at RT and 4°C for 24 hours are acceptable for additional PT, Fbg, and AT testing. Plasma samples stored 24 hours in primary tubes at 4°C are suitable for D-dimer testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 16 publications
5
16
0
Order By: Relevance
“…Several studies, including ours, observed a stability of 24 hours for PT determination of samples stored at RT, confirming the storage time given by the current CLSI guidelines. After 48‐hours to 52‐hours storage at RT, Zürcher et al observed a mean percentage decrease of 10.8%.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Several studies, including ours, observed a stability of 24 hours for PT determination of samples stored at RT, confirming the storage time given by the current CLSI guidelines. After 48‐hours to 52‐hours storage at RT, Zürcher et al observed a mean percentage decrease of 10.8%.…”
Section: Discussionsupporting
confidence: 88%
“…We studied the stability of aliquoted plasma samples stored at RT for up to 48 hours. Several studies have investigated the stability of coagulation parameters, mainly routine haemostasis parameters, in different storage conditions; however, information regarding the stability of coagulation factors studied for up to 48 hours is scarce …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were expected, given that, according to several studies and to the Clinical and Laboratory Standard Institute guidelines, coagulation cascade parameters begin to be unstable after 4–8 hours after collection and storage at 2°C‐4°C . According to these guidelines, the recommended maximum storage time of samples for the determination of PT is 24 hours at room temperature, whereas aPTT should be determined within 4 hours after collection . In the present study, we observed that PT mean values (11.2 seconds at T0 and 12.8 at T35) increased less than aPTT ones (12.5 seconds at T0 and 18.9 at T35), which is explainable with the lower stability of samples for aPTT testing than PT testing …”
Section: Discussionsupporting
confidence: 54%
“…For example, Rimac and Herak [23] examined whether fresh plasma samples stored at room temperature and at 4°C for up to 24 h after blood collection can still be accepted for additional routine coagulation testing of PT, aPTT, fibrinogen, antithrombin, and D-dimer in order to reduce unnecessary additional sampling. Salvagno et al [20] investigated the sample stability with regard to the temperature and the time before centrifugation, andvan der Meer et al [24] investigated transport conditions and light exposure in a clinical platelet study conducted in 3 countries.…”
Section: Discussionmentioning
confidence: 99%